Project management software manual - Morton, Thomas E., 1937- (Cincinnati ; London : South-Western College, 1999)
Introduction to project management. Introducing the software. The critical path method. Limited resources. Multiple projects.
Keywords: Management; Software; Industrial project management -- Software